AUDIT INTERNAL SESUAI ISO/IEC 17025:2017 BERBASIS ISO 19011:2018 : Laboratorium Pengujian Pusat Laboratorium Terpadu UIN Syarif Hidayatullah Jakarta - Dwi Ningsih, Nunung Isnaini (Jurnal Penjaminan Mutu, 2024)
Internal audit according to ISO/IEC 17025:2017 based on ISO 19011:2018 has been carried out to describe the internal audit process in laboratories that have implemented ISO/IEC 17015:2017. The internal audit is conducted on all business processes in the laboratory testing of UIN Syarif Hidayatullah Jakarta, which consists of management processes, primary processes, and supporting processes. The results of the internal audit show that in the management process there were three (3) clauses for level 2 nonconformities, in the primary process there was one (1) clause for level 1 nonconformities, two (2) clauses for level 2 nonconformities, and one (1) clause for observation. While in the supporting process, there are 1 (one) clause for observation. Based on the process, the internal audit carried out is by the audit process in ISO 19011: 2018. These findings indicate that the UIN Syarif Hidayatullah Jakarta laboratory testing has been implementing ISO / IEC 17025: 2017 even though it has not been maximal. Keywords: Audit Interal, ISO/IEC 17025:2017, ISO 19011:2018, Noncomformity